2019
DOI: 10.3892/etm.2019.7447
|View full text |Cite
|
Sign up to set email alerts
|

Pirarubicin reduces USP22 expression by inhibiting CREB‑1 phosphorylation in HeLa cells

Abstract: The expression of ubiquitin specific peptidase 22 (USP22) is upregulated in several types of cancer, and has been implicated in tumorigenesis. Pirarubicin (THP), an anthracycline antineoplastic drug, can induce apoptosis of several types of cancer cells. However, the molecular mechanisms underlying the action of THP remain to be elucidated. In the current study, treatment with THP induced HeLa cell apoptosis and decreased USP22 expression in a dose-and time-dependent manner. THP reduced the USP22 promoter-regu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 32 publications
(44 reference statements)
0
3
0
Order By: Relevance
“…As a DNA embedment agent, THP has been shown to reduce tumor activity in hepatocellular carcinoma patients [ 13 ]. Moreover, THP has also been found to possess good inhibitory effects on many kinds of tumors, such as breast cancer and cervical cancer [ 14 , 31 ]. In spite of these, the clinical application of THP is limited due to chemosensitivity resistance, which is the main cause of death in cancer patients [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…As a DNA embedment agent, THP has been shown to reduce tumor activity in hepatocellular carcinoma patients [ 13 ]. Moreover, THP has also been found to possess good inhibitory effects on many kinds of tumors, such as breast cancer and cervical cancer [ 14 , 31 ]. In spite of these, the clinical application of THP is limited due to chemosensitivity resistance, which is the main cause of death in cancer patients [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…THP has been reported capable of inducing cell apoptosis. 41 After treatment with THP@CHPS, THP@HPS, THP@HS NPs or free THP for 24 h, the apoptotic percentages of MB49 and 3T3 cells were analyzed by flow cytometry using Annexin V-FITC and PI. For MB49 cells, free THP, THP@HS, THP@HPS and THP@CHPS NPs induced 5.4, 10.5, 10.8 and 19.0% of early apoptotic cells, respectively, and 4.4, 5.0, 10.0 and 7.8% of late apoptotic cells, respectively (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…However, till now, no such specific inhibitor has been validated to target USP22. Recently, Pirarubicin (4’-O-tetrahydropyranyl doxorubicin, THP), an anthracycline (analogue of another chemotherapeutic agent known as doxorubicin), has been shown to inhibit USP22 expression in a condition-specific manner [ 87 ] . Reports indicated that protein kinase A (PKA), protein kinase B or mitogen activated kinase-mediated phosphorylation of CREB-1 bind and activate the USP22 promoter for its synthesis.…”
Section: Targeting Usp22 In Advanced Prostate Cancer Treatmentmentioning
confidence: 99%